2016
DOI: 10.1002/cncr.30189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infrared laser moxibustion on cancer‐related fatigue: A randomized, double‐blind, placebo‐controlled trial

Abstract: BACKGROUNDFatigue is the most common symptom negatively affecting the quality of life of patients with cancer. The objective of the current study was to evaluate the preliminary efficacy and safety of 10.6‐μm infrared laser moxibustion for cancer‐related fatigue (CRF).METHODSThe authors conducted a randomized, placebo‐controlled trial among 78 patients with cancer who were diagnosed with CRF. The group treated with infrared laser moxibustion received 10.6 μm of infrared laser moxibustion on the ST36 (bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…Although there were few studies with good quality evaluating the effect of moxibustion for the patients with cancer-related fatigue, a recent publication by Mao et al [32]. using infrared laser moxibustion was helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were few studies with good quality evaluating the effect of moxibustion for the patients with cancer-related fatigue, a recent publication by Mao et al [32]. using infrared laser moxibustion was helpful.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, Moran et al's response to our article does not change the conclusion of our research: infrared‐laser moxibustion has demonstrated preliminary safety and efficacy for improving cancer‐related fatigue in a Chinese patient population. Larger studies in the future with long‐term follow‐up in more racially/ethnically diverse populations are needed to confirm the benefit of this noninvasive technique for the treatment of fatigue in patients with cancer.…”
mentioning
confidence: 64%
“…We are grateful for the opportunity to respond to Moran et al's letter regarding our article . We performed repeated measures of analysis of our longitudinal data with the mixed effects linear model, but we did not present the statistical output in our article because of the journal's word limit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with interest the article by Mao et al in which they evaluate the preliminary efficacy and safety of 10.6‐μm infrared‐laser moxibustion for cancer‐related fatigue. They conclude that infrared‐laser moxibustion appears to be safe and efficacious for improving cancer‐related fatigue in a Chinese patient population.…”
mentioning
confidence: 99%